The ancient Magus' bride. Wizard's blue. Volume 5 - Sanda, Makoto; McFarlane, Ysabet Reinhardt (Seven Seas Entertainment, 2022)
Thanks to a visit to Giselle's old master, Myrtha, Ao learns about Giselle's curse and how it is tied to the city of Paris. Giselle and Ao make for Noah's church, where they hope to find the first clue to breaking the curse. But when they arrive, they find a "flamme" ravenous enough to to devour two of L'Ordre's finest.